Secure Privacy and Anonymity Setup on Hyperledger Fabric for Blockchain-enabled IoT Devices - SAAD MUHAMMAD (The Graduate School, Ajou University, 2024)
The widespread use of IoT devices has presented a significant security challenge. Main- taining privacy and anonymity within the system is desirable but comes with inevitable trade-offs such as scalability and increased complexity. The challenge lies in ensuring confidentiality and anonymity throughout the system. It is essential to safeguard privacy and anonymity, but implementing these features involves trade-offs, including scalabil- ity and increased system complexity, making these challenges seem overwhelming. To address this issue, we have developed an innovative solution for managing IoT devices using Hyperledger Fabric. Our system seamlessly integrates blockchain technology with closed-circuit television (CCTV) security cameras, particularly in rental properties. These cameras automatically adjust their feed when a new renter enters the property. To ensure secure access, we have introduced a web token for authentication purposes, enabling renters to communicate securely with property owners. Our contributions include designing an efficient framework architecture, developing a unique chain code algorithm, and integrating stealth addresses with modified ring signatures. We conducted thorough analyses, including stress testing, to demonstrate the system’s impressive throughput and minimal latency. By comparing our proposed architectures with similar existing schemes, we have effectively highlighted the advantages of our approach. Our solution significantly enhances the security of blockchain-enabled IoT devices and effectively resolves the single point of failure issue. Although we developed this system for a specific real-world area, it is scalable and applicable to other areas, such as healthcare monitoring systems, which is part of our future work.
학위논문(박사)--인공지능학과,2024. 8
Keywords: Anonymity; Blockchain; Hyperledger; IoT; Privacy; Smart Contract